INTEGRASI PENDIDIKAN SEKS PADA PEMBELAJARAN PPKn DALAM MEMBINA MORALITAS SISWA DI SMPN 4 SAPE KABUPATEN BIMA - Adi Saputra; Irsyad Dhahri; Imam Suyitno (Jurnal Tomalebbi, 2022)
Abstrack: This study aims to determine (1) To find out the strategies developed by a teacher in integrating sex education in Civics lessons. (2) To find out how the factors supporting and inhibiting sex education in Civics learning. The approach used in this research is a qualitative approach and the type of descriptive research. Sources of data obtained from schools and from informants consisting of teachers and students of SMP Negeri 4 Sape, Bima Regency. The data collection procedures used were observation, interviews, and documentation. And the data analysis techniques used consisted of data reduction, data presentation, conclusion drawing, and verification. The data obtained from the results of this study were processed using triangulation. The results of this study conclude (1) The teacher's strategy in integrating sex education in Civics learning is quite maximal, because seen from the essence and content of the material it has interrelation and interdependence relationships. And seen from the formation of cooperation between teachers, providing easy-to-understand material, as well as evaluating the performance of the work so that the results of teaching and learning activities of students are further improved in accordance with the moral values that are planted with a sexual approach and gender equality in Civics lessons compared to previously. (2) The factors that influence the integration of sex education in Civics lessons are divided into two, namely, inhibiting factors and supporting factors. As for the inhibiting factors, namely the difficulty of a teacher in adjusting the material, lack of enthusiasm and participation of students, an unclear curriculum on sex education, and the rapid development of technology that makes students easy to access sexual information so as to provide a negative perspective on sexual education so that paradoxical impression with what is conveyed by the teacher. The efforts to overcome these obstacles are: Teachers must be able to develop a Lesson Plan (RPP), learning objectivesand the benefits of learning in sex education. Because if the components are implemented properly and directed then what is the orientation of sex education will be implemented. While the supporting factors are: The existence of good support and cooperation between policy makers such as the government, school principals, professional educators in their fields, as well as making a sex education curriculum adapted to the values of Pancasila so that students are not trapped in negative things, as well as the facilities and adequate infrastructure to support students' teaching and learning activities.Keywords: Learning Orientation, Sex Education Abstrak: Penelitian ini bertujuan untuk mengetahui (1) Untuk mengetahui strategi yang dikembangkan seorang guru dalam mengintegrasikan pendidikan seks pada pelajaran PPKn. (2) Untuk mengetahui bagaimana  faktor pendukung dan penghambat pendidikan seks pada pembelajaran PPKn. Adapun pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dan jenis penelitian deskriptif. Sumber data yang diperoleh dari sekolah dan dari informan yang terdiri dari guru serta peserta didik SMP Negeri 4 Sape, Kabupaten Bima. Adapun prosedur pengumpulan data yang digunakan yaitu observasi, wawancara, dan dokumentasi. Serta teknik analisis data yang digunakan terdiri dari reduksi data, penyajian data, penarikan kesimpulan, dan verifikasi. Data yang diperoleh dari hasil penelitian ini diolah dengan menggunakan triangulasi. Hasil penelitian ini menyimpulkan (1) Strategi guru dalam mengintegrasikan pendidikan seks pada pembelajaran PPKn sudah cukup maksimal, karena dilihat dari esensi dan muatan materinya memiliki hubungan interelasi dan interdependesi. Dan dilihat dari pembentukan kerjasama antara guru, pemberian materi yang mudah dipahami, serta melakukan evaluasi kinerja terhadap hasil kerja sehingga hasil kegiatan belajar-mengajar peserta didik lebih meningkat sesuai dengan nilai-nilai moral yang ditanam dengan pendekatan seksual dan kesetaraan jender dalam pelajaran PPKn dibandingkan dengan sebelumnya. (2) Faktor-faktor yang mempengaruhi terintegrasinya pendidikan seks pada pelajaran PPKn dibagi menjadi dua yaitu, faktor penghambat dan faktor pendukung. Adapun yang menjadi faktor penghambat yaitu kesulitan seorang guru dalam menyesuaikan materi, antusias dan partisipasi peserta didik yang kurang, kurikulum yang belum jelas tentang pendidikan seks, serta berkembang pesatnya teknologi yang membuat peserta didik mudah mengakses informasi seksual sehingga memberikan cara pandang negatif terhadap pendidikan seksual sehingga berkesan paradoks dengan apa yang disampaikan oleh guru. Adapun upaya dalam mengatasi kendala tersebut yaitu: Guru harus mampu menyusun Rencana Pelaksanaan Pembelajaran (RPP), tujuan pembelajaran serta manfaat pembelajaran dalam pendidikan seks. Karena jika komponen itu dilaksanakan dengan baik dan terarah maka apa yang menjadi orientasi pendidikan seks akan terlaksana. Sedangkan yang menjadi faktor pendukungnya yaitu: Adanya dukungan dan kerjasama yang baik antara pemangku kebijakan seperti pemerintah, kepala sekolah, pendidik profesional dibidangnya, serta pembuatan kurikulum pendidikan seks disesuaikan dengan nilai-nilai Pancasila sehingga peserta didik tidak terjebak pada hal negatif, serta adanya sarana dan prasarana yang memadai untuk mendukung kegiatan belajar mengajar peserta didik. Kata Kunci: Orientasi Pembelajaran, Pendidikan Seks